2013
DOI: 10.1186/1029-242x-2013-33
|View full text |Cite
|
Sign up to set email alerts
|

Some results on the generalized Mittag-Leffler function operator

Abstract: This paper is devoted to the study of a generalized Mittag-Leffler function operator introduced by Shukla and Prajapati (J. Math. Anal. Appl. 336:797-811, 2007

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…for t > 0 and any real number σ satisfying the condition σ ≥ σ 0 > 0, where σ 0 is large enough that . It is worthwhile to mention that the detail treatment of the similar study can be found in [28,30].…”
Section: Inversion Of the Laplace Transformmentioning
confidence: 89%
“…for t > 0 and any real number σ satisfying the condition σ ≥ σ 0 > 0, where σ 0 is large enough that . It is worthwhile to mention that the detail treatment of the similar study can be found in [28,30].…”
Section: Inversion Of the Laplace Transformmentioning
confidence: 89%
“…Due to great potential and significant role of special functions especially hypergeometric functions in various problems occurring in mathematical physics, engineering [8] [9], the author has motivated to further investigate the topic. Several generalizations of hypergeometric functions have been made by many authors [10] [11]. Recently Rao [12] defined Wright type generalized hypergeometric function via fractional calculus.…”
Section: ( ) ( )mentioning
confidence: 99%
“…Several properties of Mittag-Leffler function and generalized Mittag-Leffler function can be found e.g. in [2], [5], [6], [7], [8], [10], [15], [16], [17], [18], [26], [27] and [28].…”
Section: Introductionmentioning
confidence: 99%